Other Determinants of Inflation in Nigeria - Inim, Victor; Emmanuel Samuel, Udo; Ishaku Prince , Abner (European Journal of Sustainable Development, 2020)
Inflation is a continuous macroeconomic concern that has dominated thoughts at major economic fora due to its pervasive effect on the economy. The quantity theory of money isolates money supply as the major cause of inflation. The economic reality in Nigeria contravenes the theory. The study examines other determinants of inflation in Nigeria using the autoregressive distributed lag (ARDL) method on quarterly data from January 1999- December 2018. Findings show that poor infrastructural development, exchange rate, political instability, corruption, and double taxation significantly stimulate inflation rather than just money supply. The results show a causal relationship between other determining factors and inflation. The ARDL result shows a significant long-short run relationship. The study recommends that non-monetary factors of instigating inflation should be controlled and security expenditure should be review along with-related mechanisms to achieve low inflation at single digits at most and economic growth and development. Keywords: inflation rate, money supply, Nigeria, economic indicators, ARDL Error Correction Model